Epidemiological and Geographical Profile of Gall Bladder Cancer Patients from a Hospital-based Registry of Northern Gangetic Plains - Singh, Sankalp; Bhatnagar, Sharad; Lohia, Nishant; Subramananiam, Anand; Raman, Deep; Murthy, Harish S; Prashar, Manoj; Viswanath, Sundaramm; Trivedi, Gaurav (Asian Pacific Journal of Environment and Cancer, 2022)
Purpose: Gall bladder cancer (GBC) is one of the commonest and deadliest cancers of Northern and Eastern India. The absence of a population-based cancer registry in Uttar Pradesh and Bihar has resulted in a lack of statistical information even though data from several hospital-based registries suggests that incidence rates of GBC may be one of the highest in the world. We present the four-year data on GBC from our tertiary-level multispeciality hospital. Materials & Methods: This is a retrospective and analytical study. All patients of histopathologically proven GBC over four years were included and geographic, demographic and clinical data was collected and presented. Follow up, where available, was used to assess survival at 12 months and factors affecting it. Results: A total of 245 patients with GBC were diagnosed during the study period of which more than two-thirds were women. The majority of cases at our hospital were from the state of Uttar Pradesh with the highest number coming from the Eastern districts closer to the river Ganga and its tributaries. 26.5% of cases were early stage and surgically resectable, 19.6% were locally advanced and unresectable while 53.9% were metastatic at presentation. Age, stage and radical surgery as treatment had a significant association with survival at 12 months. Conclusion: GBC has an extremely high incidence in the Northern plains of India. There is a high suspicion of its association with increasing pollution of the major rivers of the region. Early detection is crucial as definitive surgery is the only curative option with any significant improvement of survival.